Sensitivity to disgust, but not increased disgust, is associated with disapproval of gays: Experimental evidence from Turkey - Aktaş, Büşra Eylem; Tosyalı, Furkan (My University, 2024)
Previous research indicated that exposure to disgusting stimuli often leads to more negative attitudes toward gays. However, these findings primarily stemmed from Western cultures and were inconsistent. It remained uncertain whether the impact of disgust would apply to diverse cultural contexts. This study aimed to fill this gap by investigating whether the influence of disgust, previously observed, extended to an unexplored non-Western setting, Turkey. In Study 1, an online experiment was conducted to explore the connection between disgust and attitudes toward gays. Study 2 aimed to replicate these findings in a laboratory setting and examined the role of political attitudes. Study 1 found no significant link between disgust and disapproval of gays. However, in Study 2, there were significant correlations between political conservatism, disgust sensitivity, and negative attitudes toward gays. Notably, disgust did not significantly affect negativity toward gays in either study. Moreover, while political conservatism would lead to negative attitudes, it did not moderate the relationship between disgust and negativity toward gay individuals in Study 2. Present findings expand the ongoing debate about the causal role of disgust in disapproval of gays, providing original insights into a non-Western cultural context.
Keywords: Conservatism; Disgust; Disgust Sensitivity; Prejudice Toward Gay Men; Turkey